Design para comunicação: design de solução e de interação - Padovani, Stephania (InfoDesign, 2006)
FRASCARA, Jorge. Communication Design – principles, methods and practice. New York: Allworth Press, 2004. 207p. [ISBN 1-58115-365-1] Summary of the book This book is intended to outline the field of communication design, its areas of concern, its working methods, and its purposes. It is directed at visual communication design students (not at experienced designers) and includes discussions of some areas that are bound to grow and change in this era of information explosion and technological innovation. [Frascara, 2004]